Analisis Kelayakan Bisnis Ditinjau dari Aspek Pemasaran dan Keuangan Pada Kedai Olan’z Food Kebumen - Aniesatun Nurul Aliefah; Eka Arilia Nandasari (LABATILA : Jurnal Ilmu Ekonomi Islam, 2022)
This study aims to analyze the business feasibility of Olan'Z Food Stores in terms of marketing and financial aspects. This research is a qualitative field research, by taking the research object at Olan'Z Food Stores. Data collection in this study was obtained through interviews, observation, documentation with sources related to Olan'Z Food Stores, namely owners and customers. The results of the business feasibility analysis from the marketing aspect are said to be feasible, namely products that already have a brand, an attractive name, and create packaging. Affordable prices, strategic location and easy distribution, as well as attractive promotions. Analysis of business feasibility from the financial aspect results that the capital comes from the owner's capital and produces a Payback Period (PP) of 2 months and 7 weeks.